Analisis Faktor Yang Mempengaruhi Ketersediaan Tenaga Kerja Sektor Industri Wilayah Metropolitan Bandung Raya - Muhamad Wahyu Hamijaya; Heri Yanti Nadila (Jurnal Riset Ilmu Ekonomi, 2022)
The labor force participation rate is a manifestation of the amount of labor absorbed from the total working-age population. The available workforce will then occupy jobs within sectors of the national economy. In its absorption, the large-scale and medium-scale industrial sector is one of the sectors that has a massive impact on the absorption of labor from year to year. The purpose of this study is to understand the factors that affect the absorption of labor in the processing industry sector in Bandung Raya Metropolitan. The study uses quantitative analysis studies with panel data. The data processing results showed that wages, the number of business units, the amount of FDI and DDI investments had a significant positive effect on the absorption of labor in large- and medium-scale industrial sectors. On the other hand, researchers have a meeting that the disintegration of the influence of the GDRP of the industrial sector and the Human Development Index has a significant negative impact.